Economic conditions and punishment in Postbellum Georgia - Myers, Martha A. (Journal of quantitative criminology, 1991)
This paper examines the relationship between economic conditions and incarceration in Georgia between 1868 and 1936. Time-series analysis provides evidence that declining cotton prices increased the rate at which both black and white males were incarcerated. Changes in cotton production, declines in racial economic inequality, and demographic shifts also affected incarceration rates. Each had quite different implications for black and white punishment, however. The paper concludes with a discussion of the implications of these findings for research on punishment in general and Southern punishment in particular.